Immobilized and free cells of geotrichum candidum for asymmetric reduction of ketones: Stability and recyclability - Liu, Hui (2018)
Marine-derived fungus Geotrichum candidum AS 2.361 was previously reported by our group as an active strain for the enantioselective reduction of ketones. Although some other Geotrichum strains were also found from the terrestrial sources, information on their stability and reusability is scarce. Herein, the stabilities—in terms of pH tolerance, thermostability, and storage stability, and reusability—of G. candidum AS 2.361 were described for the asymmetric reduction of a series of aromatic ketones. Two differently immobilized cells (agar immobilization and calcium alginate immobilization) as well as free cells were prepared. For three substrates (1-(3-bromophenyl) ethan-1-one (1b), 1-(2-chlorophenyl) ethan-1-one (1d), and acetophenone (1g)) immobilized cells on agar showed a great improvement in the bioreduction activities compared to the free cells, increasing yields up to 97% with ee values of 99%. Cells immobilized on agar/calcium alginate could maintain more than 90% of the original activities within the assayed pH ranges of 3.5–11, while free cells were highly sensitive to alkaline and acidic conditions. Concerning thermostability, immobilized cells on agar kept 99% of their original activities after incubation at 60◦C for 1 h, while almost no activity was detected for the free cells under the same condition. Immobilized cells were stable at 4◦C for 80 days without any activity loss, while free cells started to decrease the activity after storage at 4◦C for six days. The immobilized cells retained almost 99% activity after four reuse cycles, while free cells lost almost all the activities at on the third cycle.